Efficacy and safety of sodium‐glucose co‐transporter‐2 inhibitors in type 2 diabetes mellitus: systematic review and network meta‐analysis. Issue 8 (13th May 2016) - Zaccardi, F.; Webb, D. R.; Htike, Z. Z.; Youssef, D.; Khunti, K.; Davies, M. J.
Abstract : Aim: To assess the comparative efficacy and safety of sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors in adults with type 2 diabetes. Methods: We electronically searched randomized controlled trials (≥24 weeks) including canagliflozin, dapagliflozin or empagliflozin that were published up to 3 November 2015. Data were collected on cardiometabolic and safety outcomes and synthesized using network meta‐analyses. Results: A total of 38 trials (23 997 participants) were included. Compared with placebo, all SGLT2 inhibitors reduced glycated haemoglobin (HbA1c), fasting plasma glucose (FPG), body weight and blood pressure, and slightly increased HDL cholesterol. Canagliflozin 300 mg reduced HbA1c, FPG and systolic blood pressure and increased LDL cholesterol to a greater extent compared with other inhibitors at any dose. At their highest doses, canagliflozin 300 mg reduced: HbA1c by 0.2% [95% confidence interval (CI) 0.1–0.3] versus both dapagliflozin 10 mg and empagliflozin 25 mg; FPG by 0.6 mmol/l (95% CI 0.3–0.9) and 0.5 mmol/l (95% CI 0.1–0.8) versus dapagliflozin and empagliflozin, respectively; and systolic blood pressure by 2 mmHg (95% CI 1.0–3.0) versus dapagliflozin; and increased LDL cholesterol by 0.13 mmol/l (95% CI 0.03–0.23) and 0.15 mmol/l (95% CI 0.06–0.23) versus dapagliflozin and empagliflozin, respectively. The highest doses of inhibitors had similar effects on body weight reduction. Canagliflozin 300 and 100 mg increased the risk of hypoglycaemia versus placebo, dapagliflozin 10 mg and empagliflozin 10 mg [odds ratios (ORs) 1.4–1.6]. Dapagliflozin 10 mg increased the risk of urinary tract infection versus placebo and empagliflozin 25 mg (ORs 1.4). All inhibitors similarly increased the risk of genital infection (ORs 4–6 versus placebo). Conclusions: Although they increase the risk of genital infection, SGLT2 inhibitors are effective in improving cardiometabolic markers in type 2 diabetes, with canagliflozin 300 mg performing better in this respect than other inhibitors. Further studies will clarify whether these differences are likely to translate into differing long‐term outcomes.